2004
DOI: 10.1242/jcs.01348
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide negatively regulates proliferation and promotes neuronal differentiation through N-Myc downregulation

Abstract: Nitric oxide (NO) has been found to act as an important negative regulator of cell proliferation in several systems. We report here that NO negatively regulates proliferation of neuronal cell precursors and promotes their differentiation by downregulating the oncogene N-Myc. We have studied this regulatory function of NO in neuroblastoma cell lines (SK-N-BE) and in primary cerebellar granule cell cultures. In a neuronal NO synthase (nNOS) overexpressing neuroblastoma cell line exposed to the differentiative ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
59
1
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(68 citation statements)
references
References 77 publications
7
59
1
1
Order By: Relevance
“…In embryos, NO inhibits neural precursor cell division and promotes neuronal differentiation in developing Drosophila imaginal disks (Kuzin et al, 1996) and Xenopus tadpole optic tectum (Peunova et al, 2001). A similar antiproliferative effect of NO has been reported in vitro in mammalian tumoral cell lines of neural origin (MurilloCarretero et al, 2002;Obregon et al, 1997;Peunova and Enikolopov, 1995;Phung et al, 1999) and in neuronal precursors isolated from the embryonic (Cheng et al, 2003) and neonatal (Ciani et al, 2004) brain. Additionally, several groups have shown that NO is a negative regulator of neurogenesis in the adult SVZ.…”
Section: Indexing Terms: Egf Receptor; Neural Stem Cells; Neurogenesisupporting
confidence: 58%
“…In embryos, NO inhibits neural precursor cell division and promotes neuronal differentiation in developing Drosophila imaginal disks (Kuzin et al, 1996) and Xenopus tadpole optic tectum (Peunova et al, 2001). A similar antiproliferative effect of NO has been reported in vitro in mammalian tumoral cell lines of neural origin (MurilloCarretero et al, 2002;Obregon et al, 1997;Peunova and Enikolopov, 1995;Phung et al, 1999) and in neuronal precursors isolated from the embryonic (Cheng et al, 2003) and neonatal (Ciani et al, 2004) brain. Additionally, several groups have shown that NO is a negative regulator of neurogenesis in the adult SVZ.…”
Section: Indexing Terms: Egf Receptor; Neural Stem Cells; Neurogenesisupporting
confidence: 58%
“…It has been previously demonstrated that NO acts as an important negative regulator of cell proliferation in the adult mammalian brain [41,42]. A similar anti-proliferative effect of NO has been reported in neuronal precursors isolated from the embryonic [43] and neonatal [44] brain. The observed early appearance of nitrergic cells in the RMS indicates an association between NO production and decreased proliferation induced by maternal deprivation.…”
Section: Discussionsupporting
confidence: 66%
“…In addition, the proneural basic helix-loop-helix (bHLH) transcription factor neurogenin 1 (Ngn1) promotes neuronal differentiation and suppresses formation of astrocytes (Sauvageot and Stiles, 2002). NO regulates synaptic remodeling and neuronal differentiation in the adult mammal CNS (Bicker, 2001;Ciani et al, 2004;Seidel and Bicker, 2000;Sunico et al, 2005;Truman et al, 1996). We, therefore, hypothesize, DETA-NONOate upregulates the Ncadherin/β-catenin pathway and Ngn1 expression and thereby promotes neurogenesis in both young and older rats.…”
mentioning
confidence: 99%